FEMINIST APPROACHES TO DISINFORMATION STUDIES - Marwick, Alice E.; Losh, Elizabeth; Schlüter, Maximilian; Markham, Annette; Phipps, E. Brooke (AoIR Selected Papers of Internet Research, 2023)
Disinformation, inaccurate information spread intentionally for profit, ideology, or harm is a major public issue and a significant object of study across disciplines However, much scholarship treats “disinformation” as an irritant without recognizing that it often harnesses metanarratives about inequality and identity, and disproportionately impacts marginalized communities. For example, counting how many “sockpuppet” accounts contribute to a Twitter hashtag reveals that they do not represent genuine opinions of unique individuals, but does not capture whether they advance cultural narratives about race and gender. Disinformation campaigns are also often mischaracterized as “information warfare” or “psychological operations” and reduced to military-style masculinized logics of conflict and dominance in which “threat” is framed as a matter of “cybersecurity." This leaves out complex dynamics of identity, intersectionality, affect, labor, and material infrastructures. Feminist theory, methods, and perspectives are particularly well suited to exploring such issues. This panel brings together scholars working at different edges of this nascent discipline to explore what disinformation studies can learn from feminist scholars in rhetoric, communication, and science and technology studies.